2017
DOI: 10.1186/s12887-017-0914-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual contextual factors in the validation of the Bernese pain scale for neonates: protocol for a prospective observational study

Abstract: BackgroundThe Bernese Pain Scale for Neonates (BPSN) is a multidimensional pain assessment tool that is already widely used in clinical settings in the German speaking areas of Europe. Recent findings indicate that pain responses in preterm neonates are influenced by individual contextual factors, such as gestational age (GA), gender and the number of painful procedures experienced. Currently, the BPSN does not consider individual contextual factors. Therefore, the aim of this study is the validation of the BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
0
11
0
2
Order By: Relevance
“…Crying is a common pain response in neonates and is included in several pain scales (e.g., [27, 61–63]), but some have questioned crying as an indicator of pain because it cannot be assessed in some neonates [21, 59]. Mechanical ventilation, inhibiting drugs, severe illness, and other reasons may limit the ability to cry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crying is a common pain response in neonates and is included in several pain scales (e.g., [27, 61–63]), but some have questioned crying as an indicator of pain because it cannot be assessed in some neonates [21, 59]. Mechanical ventilation, inhibiting drugs, severe illness, and other reasons may limit the ability to cry.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates were recruited by consecutive sampling and then stratified according to GA at birth [27]. Trained study assistants in each study centre identified potentially eligible neonates and informed their parents of the aim and purpose of the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Swaddling/tucking was found to be effective in reducing pain in premature infants (5). In recent years, a series of observational tools have been developed to measure stress and pain (6,7). The comfort scale which is well-known multidimensional tool, is originally developed as a continuous measure of distress, sedation and pain in nonverbal pediatric patients aged from birth to 18 years (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…A dor gera desconforto, estresse e irritabilidade especialmente em unidades de internação neonatal. Os fatores contextuais a dor do neonato englobam: maturidade, estado de saúde, ambiente, equipe que presta cuidados, além de experiência anterior com a dor ou a duração da hospitalização (MELO; CARDOSO, 2017;CIGNACCO et al, 2017).…”
Section: Introducãounclassified